Alveolar soft part sarcoma of the orbit, a case report of a rare tumor - Nava-Castañeda, Ángel; Tovilla-Canales, José Luis; Zuazo, Francisca; Rodríguez-Cabrera, Lourdes; Garnica-Hayashi, Lilia (Nepalese Journal of Ophthalmology, 2017)
Background: Alveolar Soft Part Sarcoma is a rare malignant tumor of uncertain histogenesis, representing 0.5-1% of all soft tissue tumors. It occurs predominantly in head and neck regions, especially the orbit and the tongue, in infants, causing no specific symptoms for an extended period of time. Case: A four year old girl was brought to consultation because of persistent swelling of her left upper and lower eyelid for the past six months. A 4 mm proptosis was noted on her left eye with significant upwards displacement of the globe. A firm, not pulsating and non tender mass was palpated, and motility examination revealed deficient abduction and infraduction. Visual acuity was 20/40 and 1/200 in the right and left eye, respectively. The computed tomography revealed an extraconal mass on the inferotemporal aspect of the left orbit, with no bony erosion or globe invasion. An excisional biopsy was made, finding a tumor with nests of clusters of large polygonal cells, separated by fibrous septa and a sinusoidal vascular channel. An Alveolar Soft Part Sarcoma was diagnosed. Our patient had a favorable post-operative follow up, and oncologic evaluations have not shown metastasis or local recurrences. Observations and Conclusions: Alveolar Soft Part Sarcoma is a rare malignant tumor of indolent course, but with propensity to distant metastases, making early diagnose and long term follow up necessary.